2014
DOI: 10.1007/s11357-014-9634-3
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific thigh muscle loss as an independent phenomenon for age-related muscle loss in middle-aged and older men and women

Abstract: The purpose of this study was to examine the relationships between dual-energy X-ray absorptiometry (DXA)-determined appendicular lean mass (aLM) and ultrasound-measured thigh muscle thickness (MTH) ratio and between aLM or thigh MTH ratio and zigzag walking performance. Eighty-one middleaged and older adults (41 men and 40 women) aged 50 to 74 years volunteered for the study. Approximately two thirds of the subjects (34 men and 17 women) carried out regular sports activity (at least >2 times a week) including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 25 publications
6
44
0
Order By: Relevance
“…11 Similarly, isokinetic knee extension strength decreased significantly at follow-up, while no significant change was observed in isokinetic knee flexion strength. 11 In line with the results of that study, a limited number of studies have reported that an age-related site-specific thigh muscle loss is observed not only in Japanese men and women 12,13 but also in German and American men and women 14,15 . This site-specific anterior thigh muscle loss is associated with decreasing zigzag walking performance, but not straight walking performance in middle-aged and older men and women.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…11 Similarly, isokinetic knee extension strength decreased significantly at follow-up, while no significant change was observed in isokinetic knee flexion strength. 11 In line with the results of that study, a limited number of studies have reported that an age-related site-specific thigh muscle loss is observed not only in Japanese men and women 12,13 but also in German and American men and women 14,15 . This site-specific anterior thigh muscle loss is associated with decreasing zigzag walking performance, but not straight walking performance in middle-aged and older men and women.…”
Section: Introductionsupporting
confidence: 87%
“…13,15,26 However, the difference between assessing single and multidimensional variables is not well known. To compare MRI/CT studies with ultrasound studies, we calculated the ratio of quadriceps to hamstring muscle CSA or MV for MRI/ CT studies and the ratio of anterior to posterior MT for ultrasound studies (Table 2).…”
Section: Indexes For Evaluating Age-related Site-specific Muscle Lossmentioning
confidence: 99%
“…This sitespecific muscle loss is observed not only in Japanese men and women (4), but also in German and American men and women (2,7). Evidence exists suggesting that site-specific muscle loss may occur independently of the age-related muscle loss detected at the whole-body level (7). Site-specific thigh muscle loss may be associated with the development of physical disability in older adults (6).…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, there is a greater loss of muscle in the anterior thigh than in the posterior thigh (1,13,21,23), which is defined as site-specific muscle loss (5,8). This sitespecific muscle loss is observed not only in Japanese men and women (4), but also in German and American men and women (2,7). Evidence exists suggesting that site-specific muscle loss may occur independently of the age-related muscle loss detected at the whole-body level (7).…”
Section: Introductionmentioning
confidence: 99%
“…In general, it is well known that the loss of skeletal muscle strength and size with increased age (sarcopenia) is greater in the lower limbs than in the upper limbs (18-88 years [4]; 20-89 years [5]). In addition, recent studies revealed that the sarcopenia is muscle specific and that greater knee extensor muscle loss was found in older adults [6][7][8]. Therefore, periodic assessment of knee extensor muscle strength and size is important for all ages to evaluate the functional status of individuals and to identify and Corresponding author: Tomohiro Yasuda, Ph.D., associate professor, research field: exercise physiology.…”
Section: Introduction mentioning
confidence: 99%